An extended approach to value chain analysis - Klemen Knez; Andreja Jaklič; Metka Stare (Journal of Economic Structures, 2021)
In the article, we propose a comprehensive methodology of value chain analysis in the international input-output framework that introduces a new measure of value chain participation and an extended typology of value chains, with the novel inclusion of domestic value chain to address the extent of fragmentation of purely domestic production. This allows for the simultaneous analysis of both global and domestic production fragmentation, the complex patterns of their evolution and their impact on economic development. The main contribution of the proposed methodology is conceptual: it permits the measurement of all value chain paths that pass through each country-sector from production to final consumption, whether the path includes downstream linkages, upstream linkages or their combination. Empirical application of this methodology shows the importance of including domestic fragmentation in value chain analysis: The fragmentation of both global and domestic levels of production has a significant positive correlation with economic growth. This implies that the effects of global production fragmentation must be analysed together with the changing structure of the fragmentation of domestic production to obtain the whole picture, one that might provide important information for policymaking and industrial policy.
Keywords: F1; F4; F6; 330; Domestic value chain; Global value chain; Input-output framework; Participation rate; Value chain typology; Value chains